Estimasi Kebutuhan Dimensi Bangunan Penangkap Sedimen pada Saluran Drainase Kota Cirebon Menggunakan Analisis Hidrologi dan Metode USLE - Prastica, Rian Mantasa Salve; Setyoasri, Yosephina Puspa (Indonesian Society of Applied Science, 2022)
Sediment carried by water is one of the problems that has a negative impact on aquatic ecosystems, especially if the water is used for public consumption. One of the mitigations that can be done is the construction of a sediment trap building so that the water does not contain a lot of solids containing polluting waste nutrients. In this study, the dimensions of the sediment catchment building in Cirebon City were estimated using hydrological analysis and basic hydraulics as research methods. The estimation of erosion and sedimentation rates was carried out using the USLE method. From the results of the analysis, the dimensions of the sediment catcher are required with a height of 2.5 meters and a bottom width of 7 meters and an estimated length of a sediment catcher of 250 meters. Suggestions for future research, it is hoped that the estimation of the construction of this sediment catcher uses a program or analytical tool so that the estimation results are more accurate and effective when implemented in the field.